Vademecum contemporary history Czech Republic : a guide to archives, research institutions, libraries, associations, museums and places of memorial / edited by, Oldrich Tuma, Jitka Svobodová, Ulrich Mählert - Tuma, OldrichSvobodová, JitkaMählert, Ulrich (1968-)
Contiene directorios de archivos, bibliotecas, museos, medios de información, asociaciones y centros de educación e investigación de la República Checa